Efeitos dos Programa Agroamigo e Bolsa Família na redução da inadimplência dos agricultores do PRONAF B nos municípios piauienses - Alencar, Paulo Regis Machado de (2010)
This study aimed to ascertain the effects of Microcredit Programs Rural - Agroamigo and Conditional Cash Transfer FAMILY SCHOLARSHIP in Reducing Delinquency Farmers PRONAF B municipalities in Piaui, through analysis of data from recipients of Family Allowance Program in the state Piaui, from the Ministry of Social Development - and MDS data file Hiring also in the municipalities in Piaui, the program Agroamigo / Pronaf Banco do Nordeste, plus entries, reports and monitoring reports from customers. We used an econometric model consisting of a Logit regression, called Model Likelihood Delay PRONAF B with Farmers in the state of Piaui. For the present study were used variables Public Policy Variables characteristics of the Individual / Family Variables and Variable Funding characteristics, characteristics of Business / Activity, however, more emphasis was given to the Public Policy Variables: Agroamigo STOCKS AND FAMILY. The highlight among the variables of Public Policy was the variable that showed Agroamigo substantial effect in reducing Default PRONAF B, showing a significant, implying that participation in this program reduces the probability of default at 27%, while the variable has FAMILY SCHOLARSHIP. Default-lowering effect of only 4%, which leads us to conclude that the policy guidance and monitoring technique that constitute strong pillars of the Methodology Programme Agroamigo produce more effects on the Default PRONAF B of the Policy Conditional Cash Transfer BOLSA FAMÍLIA.